Epidemiological profile of leprosy in the elderly in a microregion, state and northeast region from 2012-2021 (Research, Society and Development, 2022)
This researh aims to identify the rate of reported cases of leprosy in the elderly in a micro-region of the interior of Paraíba, as well as the state itself and the Northeast region in Brazil, in the years 2012 to 2021. Ecological study with a quantitative approach that aimed to identify the rate of reported cases of leprosy in the elderly in a micro-region of the interior of Paraíba, as well as the state and the Northeast region, in the years 2012 to 2021. The information was collected through secondary data made available by the Department of Informatics of SUS (DATASUS), on the website of the Ministry of Health. The data were obtained from the Information System of Notifiable Diseases (SINAN) and the variables chosen for analysis were: year, gender, age group, type of leprosy diagnosed, type of treatment diagnosed and type of treatment updated/performed. It was found that the main information found show a higher rate of cases in males, 60-79 years old and multibacillary, pointing to the need for training of professionals in order to facilitate the diagnosis; as well as home visits by the health team, as an important tool in maintaining control of new or existing cases, in addition to the development of educational activities in order to use the exchange of information as an aid to possible diagnosis of cases, as well as to demystify the disease for the general population.